Economical Operation and Hazardous Air Pollutant Emissions of Biodegradable Sludge Combustion Process in Commercial Fluidized Bed Plant - Ha-Na Jang; Myung Kyu Choi; Hang Seok Choi (Energies, 2024)
Waste sludge is characterized by high moisture, volatile compounds, toxic compounds, and ashes. The efficient operation of a commercial fluidized bed combustion (FBC) plant is important for reducing operational costs. We selected a commercial FBC plant for industrial waste sludge combustion to investigate the mass balance of the FBC process and the performance of the air pollution control device. Based on fuel analysis, the flow rate of incineration air was calculated as 4567 Nm3/h. After FBC combustion, the flow rate of the incineration gas increased to 8493.8 Nm3/h. Analysis of the heat balance showed that some heat potential was lost through leakage during the combustion process. The temperature of the incineration gas decreased to 200 °C at the inlet of the air pollution control device. According to the hazardous air pollutant emission testing of sampling points, the operation factors of lime slurry injection for SOx and HCl in the semi-dry reactor were 64.20 and 4.81 kg/h, respectively. In the wet scrubber, the operation factors of NaOH for SOx and HCl were 23.88 and 3.14 kg/h, respectively. At these operation factors, the available waste generation in the semi-dry reactor and wet scrubber was optimized to 76.6 and 42.57 kg/h, respectively.